Distribution of Diagnoses and Clinical and Imaging Characteristics in 1,322 Consecutive Suspected Stroke Patients - Sporns, Peter B.; Brehm, Alex; Hilgers, Caroline; Ntoulias, Nikolaos; Tsogkas, Ioannis; Psychogios, Marios (Frontiers in Neurology, 2021)
Background Endovascular thrombectomy (EVT) has become standard of care for large vessel occlusion strokes but several barriers for implementing an optimal organization of stroke management remain. Major issues include the lack of reliable data on the percentage of stroke patients potentially eligible for EVT especially in times of expanding indications for EVT. Our aim was therefore to study the frequencies of possibly EVT eligible patients such as patients with medium vessel occlusions, patients with low Alberta Stroke Program Early Computed Tomography Scores (ASPECTS), patients presenting in an extended time-window after onset of symptoms and patients with mild symptoms at presentation (National Institutes of Health Stroke Scale, NIHSS ≤ 5). We also give detailed imaging and clinical information about the patients presenting with intracranial hemorrhage and other ischemic stroke mimics stratified by symptoms at presentation. Methods Cohort-study of all consecutive patients with suspected acute stroke presenting to a tertiary care center in Germany between 1st September 2016 and 31st August 2017. Baseline and follow-up clinical and imaging characteristics were collected from patients’ medical charts. Results Of 1322 patients with a suspected acute stroke, 592 (44.8%) had ischemic strokes, 221 (16.7%) hemorrhagic strokes, 190 (10.9%) transient ischemic attacks (TIAs) and 319 (24.1%) were classified as stroke mimics. Stroke severity was mild (NIHSS ≤ 5) in 866 (65.5%), 15.7% of the patients with an occlusion of the anterior circulation had an ASPECTS ≤ 5, 17.4% of the patients with an ischemic stroke had distal vessel occlusions and 49% of the patients presented later than 6 hours after onset of symptoms. Conclusion Our results help to plan resources in thrombectomy-capable centers in times of expanding indications for EVT where resources will have to be adjusted to patients with low-NIHSS, low-ASPECTS, distal occlusions and patients presenting in the extended time-window, which may altogether account for additional 20% of all ischemic stroke patients.